Analyze One Issue Faced by The Company and Then Provide Relevant Solution - Wen, Ng Yi; Kee, Daisy Mui Hung; Ling, Koid Wang; Xuang, Ng Sok; Kai, Yang; Alfertaj, Eman (AIBPM Publisher, 2019)
This report is about a study on analyzing one issue faced by the company and provide some relevant recommendations to solve the problem. The company we chose is Kopitan Classic Penang Delight which is a well-known food and beverage chain business model in Malaysia. Customers satisfaction is the most common and important criteria in any organization particularly in food industry. Due to the market competition, a company should always focus on the needs and wants of the target customers to ensure that the customers are satisfied with their product and services. The company should able to adapt the changes of the demand of customer in order to sustain in the market. Besides focus on the external factor, the internal control is also vital to build a good reputation of company. The training of workers and their attitude gives an important impact on whether the customers are satisfied with the service provided by the company. The well management of an organization can attract more customers and contribute to a higher profit. There is some methodology employed in this research. The main issue faced by the company is illustrated in the results of analysis and finding. After identifying the issue, a few steps are recommended so that the company can apply to overcome it.